Preparation of Polyaniline Nanocomposites Using Various Surfactants - Sadegh Nabizadeh1, Mohammad; Mokhtarifar1, Mojtaba; Eisazadeh2, Hossein (Asian Journal of Chemistry, 2011)
In this study, polyaniline nanocomposites were prepared in aqueous and aqueous on-aqueous media by using ammonium peroxy disulphate as an oxidant in presence of various surfactants such as sodium dodecylbenzenesulfonate and hydroxypropyl cellulose. Morphology, particle size, yield and chemical structure of products were characterized by using scanning electron microscope and fourier transform infrared. The results indicate that the morphology, yield and particle size of products are dependent on the type of surfactant. The results also show that the intensity of peaks is dependent on the type of surfactant.